PENGARUH FAKTOR FUNDAMENTAL TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Yastini, Ni Putu Yeni Ari; Mertha, I Made (E-Jurnal Akuntansi; Vol 11 No 2 (2015), 2015)
The purpose of this research is to examine the effect of Leverage (DER), Dividend Policy (DPR), Profitability (ROA) to firm value at Manufacturing and Mining Companies Listed on BEI Period 2010– 2011, using  multiple linear regression analysis. The results of this research show that DER variable have positive significant to firm value, DPR have not significant effect but have positive coefficient firm value meanwhile profitability variables are shown to have a negative significant effect on firm value.
Keywords: Firm Value, Leverage, Dividend Policy, Profitability